Developing Preschool Teachers’ Computational Thinking Knowledge, Attitudes, Beliefs, and Teaching Self-Efficacies: A Curriculum-Based Professional Development Program - Saxena, Anika; Chiu, Ming Ming (Frontiers in Education, 2022)
Grounded in transformative teacher development through the curriculum-based professional learning (CBPL) approach to teaching-learning, this exploratory study surveyed the computational thinking (CT) views of 25 in-service teachers before and after their CT professional development programme workshops. Multivariate outcome multilevel cross-classification analysis showed that after their workshops, these teachers changed their CT knowledge, CT attitudes, CT beliefs, and CT teaching self-efficacy. Teachers reporting greater CT knowledge than others felt greater overall CT teaching self-efficacy, including for both plugged and unplugged CT activities. Moreover, teachers who reported a school culture of sharing and teamwork or sufficient school resources for CT activities were more likely than other teachers to have greater teaching self-efficacy for plugged CT activities or CT activities overall. These results highlight the importance of school culture, school technology resources, and teachers’ reported CT knowledge to their CT teaching self-efficacy.